Podoplanin: emerging functions in development, the immune system, and cancer - Astarita, Jillian L.; Acton, Sophie E.; Turley, Shannon J. (Frontiers in Immunology, 2012)
Podoplanin (PDPN) is a well-conserved, mucin-type transmembrane protein expressed in multiple tissues during ontogeny and in adult animals, including the brain, heart, kidney, lungs, osteoblasts, and lymphoid organs. Studies of PDPN-deficient mice have demonstrated that this molecule plays a critical role in development of the heart, lungs, and lymphatic system. PDPN is widely used as a marker for lymphatic endothelial cells and fibroblastic reticular cells of lymphoid organs and for lymphatics in the skin and tumor microenvironment. Much of the mechanistic insight into PDPN biology has been gleaned from studies of tumor cells; tumor cells often upregulate PDPN as they undergo epithelial-mesenchymal transition and this upregulation is correlated with increased motility and metastasis. The physiological role of PDPN that has been most studied is its ability to aggregate and activate CLEC-2-expressing platelets, as PDPN is the only known endogenous ligand for CLEC-2. However, more recent studies have revealed that PDPN also plays crucial roles in the biology of immune cells, including T cells and dendritic cells. This review will provide a comprehensive overview of the diverse roles of PDPN in development, immunology, and cancer.